(Re)evaluating language attitudes on Indonesian tourism website: A study on ecolinguistics - Arina Isti'anah (Universitas Syiah Kuala, 2020)
Tourism is one of the government’s ways of promoting the country’s identity and improving its economic growth. For tourists, it is to find not only reliable information but also promotion and the existence of the website is effective to persuade the potential tourists. The presence of nature’s beauty is an overwhelming source of curiosity for visitors. The popularity of Indonesian tourism has motivated scholars to research tourism discourse strategies, yet the study on how nature was represented on the tourism website is still scarce. By applying Critical Discourse Analysis, this paper attempts at (re)evaluating language attitudes of the ecolexicon on the Indonesian tourism website. The research problems are formulated to answer (1) what domains of the environment are presented on the website, (2) how the ecolexicon found is evaluated, and (3) how the environment should be described on the website. The data were taken from 16 destination texts accessed from www.indonesia.travel. This research found that the physical environment comprising various domains dominated the website in the form of appreciation. The domination of valuation on the website revealed that Indonesian nature was promoted in terms of its value. It persuaded potential tourists to adore the beauty of the Indonesian physical environment. The website was re-evaluated to promote not only the physical environment but also social and economic environments in the form of judgment. The absence of judgment needs to be considered by the government considering that tourism should be a good chance to teach people how to respect nature despite people’s excitement when visiting the tourism destinations.